Pengaruh biosin dan ekstrak cente terhadap perkembangan Aphis glycines (Homoptera : Aphididae) - Harnoto Harnoto; Dodin Koswanudin; Asep Nugraha Ardiwinata (Perhimpunan Entomologi Indonesia, 2004)
A study was conducted at Engineering of protein and Immunology. Division, Research Institute for Agricultural Biotechnology and Genetic Resources Bogor during 2000, to determine the effect of Biosin and Lantana camara seed extracts on development of Aphis glycines A. completely randomized design was used with four replications. Treatment consisted of three concentrations of Biosin and two concentrations of L camara seed extracts and untreated (control). Thirty days old soybean plant in plastic pots were applied according to its treatments. Biosin and L camara seed extracts were used as foliar spray. Volume of spray solution was 7.5 ml/pot. Half an hour after application, soybean plants were infested by 20 third instar A. glycines each pot. The result showed that Biosin and L. camara seed extracts decreased the development of A. glycines populations, especially Biosin and L camara seed extracts 0.4%.